Impact of Brexit on International Litigation - Okinčic, Sebastjan (Teisė, 2023)
By concentrating on the few recognised instruments of private international law, the article analyses problems in international commercial dispute resolution arising from Brexit. In particular, the paper deals with the relevance of, firstly, the 2007 Lugano Convention on jurisdiction and the recognition and enforcement of judgments in civil and commercial matters; secondly, the 2005 Hague Convention on Choice of Court Agreements; and, thirdly, the 2019 Hague Convention on the Recognition and Enforcement of Foreign Judgments in Civil or Commercial Matters, all in the context of Brexit. Contextual analysis of each of the said instruments pays particular attention to the challenges specific to each of them. Therefore, for example, the article discusses the EU’s arguments in relation to its refusal to allow the United Kingdom to join the aforementioned 2007 Lugano Convention as well as varying perspectives on the moment when the 2005 Hague Convention begins to apply to the United Kingdom. Finally, the paper discusses the relevance of the recent 2019 Hague Convention in the context of Brexit.